Integrated, multidisciplinary care for hand eczema: design of a randomized controlled trial and cost-effectiveness study - Boot Cécile RL; Bruynzeel Derk; Coenraads Pieter J; van der Valk Pieter GM; van Gils Robin F; van Mechelen Willem; Anema Johannes R (BMC, 2009)
Abstract Background The individual and societal burden of hand eczema is high. Literature indicates that moderate to severe hand eczema is a disease with a poor prognosis. Many patients are hampered in their daily activities, including work. High costs are related to high medical consumption, productivity loss and sick leave. Usual care is suboptimal, due to a lack of optimal instruction and coordination of care, and communication with the general practitioner/occupational physician and people involved at the workplace. Therefore, an integrated, multidisciplinary intervention involving a dermatologist, a care manager, a specialized nurse and a clinical occupational physician was developed. This paper describes the design of a study to investigate the effectiveness and cost-effectiveness of integrated care for hand eczema by a multidisciplinary team, coordinated by a care manager, consisting of instruction on avoiding relevant contact factors, both in the occupational and in the private environment, optimal skin care and treatment, compared to usual, dermatologist-led care. Methods The study is a multicentre, randomized, controlled trial with an economic evaluation alongside. The study population consists of patients with chronic, moderate to severe hand eczema, who visit an outpatient clinic of one of the participating 5 (three university and two general) hospitals. Integrated, multidisciplinary care, coordinated by a care manager, including allergo-dermatological evaluation by a dermatologist, occupational intervention by a clinical occupational physician, and counselling by a specialized nurse on optimizing topical treatment and skin care will be compared with usual care by a dermatologist. The primary outcome measure is the cumulative difference in reduction of the clinical severity score HECSI between the groups. Secondary outcome measures are the patient's global assessment, specific quality of life with regard to the hands, generic quality of life, sick leave and patient satisfaction. An economic evaluation will be conducted alongside the RCT. Direct and indirect costs will be measured. Outcome measures will be assessed at baseline and after 4, 12, 26 and 52 weeks. All statistical analyses will be performed on the intention-to-treat principle. In addition, per protocol analyses will be carried out. Discussion To improve societal participation of patients with moderate to severe hand eczema, an integrated care intervention was developed involving both person-related and environmental factors. Such integrated care is expected to improve the patients' clinical signs, quality of life and to reduce sick leave and medical costs. Results will become available in 2011.